2003
DOI: 10.1038/sj.bjc.6600727
|View full text |Cite
|
Sign up to set email alerts
|

The precancer risk of betel quid chewing, tobacco use and alcohol consumption in oral leukoplakia and oral submucous fibrosis in southern Taiwan

Abstract: In areas where the practise of betel quid chewing is widespread and the chewers also often smoke and drink alcohol, the relation between oral precancerous lesion and condition to the three habits is probably complex. To explore such association and their attributable effect on oral leukoplakia (OL) and oral submucous fibrosis (OSF), a gender -age-matched case -control study was conducted at Kaohsiung, southern Taiwan. This study included 219 patients with newly diagnosed and histologically confirmed OL or OSF,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
180
5

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(208 citation statements)
references
References 20 publications
14
180
5
Order By: Relevance
“…In our study, a 2.9-and 2.2-fold elevated risk of contracting esophageal cancer was found to relate to areca nut chewing with a piece of Piper Betel Linn inflorescence and with betel leaf/stem and inflorescence mixed, respectively; both types of products do not use tobacco as an ingredient in Taiwan. 4,9 Comparable results were reported by studies conducted in 2 areas of India, 15,23 in those studies a 1.6 -2.2-fold increase risk for esophageal cancer was observed among chewers without tobacco. These findings suggest that chewing products without tobacco was an independent risk factor for squamous cell carcinoma of the esophagus.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In our study, a 2.9-and 2.2-fold elevated risk of contracting esophageal cancer was found to relate to areca nut chewing with a piece of Piper Betel Linn inflorescence and with betel leaf/stem and inflorescence mixed, respectively; both types of products do not use tobacco as an ingredient in Taiwan. 4,9 Comparable results were reported by studies conducted in 2 areas of India, 15,23 in those studies a 1.6 -2.2-fold increase risk for esophageal cancer was observed among chewers without tobacco. These findings suggest that chewing products without tobacco was an independent risk factor for squamous cell carcinoma of the esophagus.…”
Section: Discussionmentioning
confidence: 70%
“…As reported in our previous studies, smoking not only explains about 62.0% of lung cancer in men in Taiwan, 33 but combining with betel quid chewing, the 2 factors account for 86.5% of oral precancer (oral leukoplakia or submucous fibrosis). 9 Avoidance or cessation of use of these substances would greatly benefit the health of the residents in Taiwan. Although approximately 36% of cancer cases in our study were excluded from the final data analyses, similar patterns for selected demographic factors, such as age and gender between recruited and non-recruited patients were detected in each geographic area. Education in the present study was found to strongly relate to risk of esophageal caner.…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco and alcohol have been established as risk factors for the development of such potentially malignant and malignant disorders of the oral mucosa (Jaber et al, 1999;Moreno-Lopez et al, 2000;Lee et al, 2003;Znaor et al, 2003;Saraswathi et al, 2006;Yen et al, 2007;Cebeci et al, 2009;Javed et al, 2010). In South India chewing betel quid/ paan (betel leaf enclosing sliced areca nut, catechu, lime and various other spices which may or may not contain tobacco) (Warnakulasuriya et al, 2002;Rani et al, 2003;Aruna et al, 2011) is a common habit but the evidence for cancer occurrence due to this habit without tobacco is limited (Znaor et al, 2003;Lee et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…2,[4][5][6][7] Betel nut contains unique alkaloid, and its major constituents -arecoline and arecaidine -are capable of inhibiting g-aminobutyric acid (GABA) receptor. 8 The previous researches suggest that betel nut chewing can increase body mass index (BMI) 9 or contribute to central obesity.…”
Section: Introductionmentioning
confidence: 99%